PTH-183 The Diagnostic Utility of Endoscopic Duodenal Biopsies for Gastrointestinal Investigation. (4th June 2013) - Patel, N; Blackwell, V J; Patel, P; Walker, M M; Williams, H R
Abstract : Introduction: Duodenal biopsies are usually taken at upper gastrointestinal endoscopy to exclude coeliac disease (CD). To date, few studies have investigated overall duodenal pathologies in this group. Serological testing for anti-tissue transglutaminase antibodies (TTG) should be performed in patients with a diagnosis of lymphocytic duodenosis (LD), which may herald CD. The main objectives of this study were to determine the indications and histological findings for duodenal biopsies in a teaching hospital setting, and the prevalence of LD and new diagnoses of CD in this cohort. Methods: 1043 patients with duodenal biopsies taken during upper gastrointestinal endoscopy in a teaching hospital setting in 24 months (2009–11) were studied retrospectively. Demographics, indications and histological findings were documented. Patients with known CD were excluded from the study; if an individual had more than one biopsy in the time period then only the first biopsy was included. When a specific abnormality was targeted for biopsy this was recorded. For LD patients, TTG results were recorded where available. Results: The patients' median age was 60 (range 16–97); 55% were female. Anaemia was the commonest indication for biopsy (in 51% of patients) followed by weight loss and abdominal pain. 76% of biopsies were normal. LD was found in 155 patients (15%), of whom 64% were female. Biopsy appearances of CD with positive TTG were found in 13 patients (1.2%). Documentation of serology was not always available and so the incidence of CD in this population may be underestimated. Crohn's disease was diagnosed in 3 biopsies (0.29%). Graft versus host disease, drug effect, lymphangiectasia and infection were seen (1 Giardia, 1 atypical mycobacteria, 1 Strongyloides). 70 duodenal biopsies (7%) targeted specific abnormalities, including 6 malignancies (3 adenocarcinoma, 1 carcinoid tumour and 1 lymphoma) and 6 benign polyps including 2 adenomas. Of the 973 non-targeted biopsies, 772 (79%) were normal. There were no statistical differences between positive biopsy results and specific indications. Conclusion: Whilst the majority of biopsies were normal, significant abnormalities were found in 24% and LD was present in 15%. While important for the diagnosis of CD, duodenal biopsy was also vital for the diagnosis other pathologies including infection, Crohn's disease, drug effect and tumours. Disclosure of Interest: None Declared.